Gemella morbillorum mitral valve endocarditis in a patient with a history of mitral valve annuloplasty. Issue 4 (29th April 2022) - Liu, Charles Ruohua; Heid, Christopher A; Chandra, Raghav; Hauptmann, Edward; Brickner, Mary Elizabeth; Hwang, Michael; Wait, Michael A
Abstract : A woman with a history of congenital heart disease status post multiple valve operations including mitral valve repair presented with 2 months of low back pain and general malaise. Blood cultures returned positive for Gram-positive cocci. While transthoracic echocardiography did not identify vegetations, transoesophageal echocardiography visualised vegetations on the patient's mitral valve, which had previously undergone repair with annuloplasty. The patient was found to have infectious endocarditis (IE), caused by Gemella morbillorum . The patient was treated with over 6 weeks of intravenous antibiotics. Cases of Gemella -associated IE are rare and largely relegated to case reports. This report aims to contribute to the literature regarding this subject, and to further characterise the presentation and treatment of Gemella -associated IE. Additionally, this report emphasises the importance of maintaining a high suspicion of IE in a patient with non-specific malaise in the setting of prior cardiac valve operation.